Extraction et étude physico-chimique d’une huile végétale extraite à partir d’une Oléagineuse Tournesol (Helianthus Annus) - Djaafeur Djebbar, Yousra (My University, 2025)
The research focused on the extraction and utilization of sunflower oil (Helianthus Annuus), highlighting its physicochemical characteristics and its use in soap production. The use of a Soxhlet apparatus with an organic solvent resulted in a highly pure oil with optimal yield. Analysis of the oil revealed a significant concentration of unsaturated fatty acids, particularly linoleic acid, which provides nutritional and emollient properties beneficial for moisturizing and cosmetic treatments. Physicochemical evaluations revealed several crucial indicators: density (0.918–0.923 g/cm³), refractive index (1.464–1.470), and saponification value (193.014 mg KOH/g), which demonstrate its ability to be transformed into soap. The hot- process saponification method produced a mild, moisturizing soap. However, it exhibited low lather and intermediate hardness, requiring modifications to optimize its robustness and stability. Several approaches were considered to improve the soap's quality: the integration of additional oils (coconut, castor) to intensify the lather, as well as the addition of antioxidants (vitamin E) to prevent rancidity caused by the oxidation of unsaturated fatty acids. Finally, a technical and economic analysis was proposed to assess the industrial viability of the production process, including material costs, sales prices, and market penetration for natural cosmetic products. This study highlights the potential of sunflower oil in the manufacture of mild, moisturizing soaps, while emphasizing the need to optimize formulations to strengthen its sustainability and competitiveness.
Keywords: Extraction, Soxhlet, sunflower oil, linoleic acid, saponification, physiochemistry, foam, hardness, antioxidants, cosmetics, technical-economic aspect.